RESTORATIVE JUSTICE IN CRIMINAL ACTS OF DAMAGE OF MINDFUL GOODS: RESTORATIVE JUSTICE DALAM TINDAK PIDANA PERUSAKAN BARANG RINGAN - Defi Harahap, Syarah (LPPM UPMI, 2023)
Destroying other people's property is very detrimental to the owner of the goods, whether the goods are damaged only partially or completely, so that the owner of the goods can no longer use his property. Factors that influence a person to commit a crime are psychological and environmental factors. Destruction is ensnared in Article 406 of the Criminal Code and those who are classified or considered as non-criminal perpetrators are at least 4 types as regulated in Article 55 of the Criminal Code. This research was made aiming to explain criminal responsibility for the destruction of light goods based on the concept of justice. This research method uses qualitative methods with a normative approach such as through laws and library approach. The data used is secondary data consisting of primary, secondary and tertiary legal materials. The results of the study show that in order to achieve justice, the punishment for the perpetrators of the destruction of goods is compensation for the victim.